The Political Economy of Sovereign Defaults - Andreasen, E (Elsevier B.V., 2019)
How do income distribution and the tax system affect sovereign borrowing and default decisions? Are these effects shaped by the political constraints that governments face when raising revenues to repay the debt? To address these questions, we incorporate agent heterogeneity, in terms of income distribution and tax burden, and a political support constraint into a standard DSGE model of sovereign default. The results show that income inequality and regressive taxes make defaults more likely for a given level of debt while they reduce sovereign borrowing in equilibrium. Tighter political support requirements reinforce these effects. © 2018 Elsevier B.V.